Design and evaluation of mega container terminal configurations: An integrated simulation framework. (June 2013) - Sun, Zhuo; Tan, Kok Choon; Lee, Loo Hay; Chew, Ek Peng
Operators of busy container terminals need to periodically evaluate options for capacity expansion in order to meet the increasing demands for container handling at their terminals. When planning such capital intensive investments, it is important to find an efficient and effective way to design and evaluate various possible terminal layout and equipment configurations. The issue is further complicated for mega-sized container terminals which consist of multiple berths and yards due to pre-existing geological conditions. This paper proposes an integrated simulation framework to facilitate the design and evaluation of mega container terminal configurations with integrated multiple berths and yards. There are two major components in this framework: a geographical information system (GIS) and a multi-agent system (MAS). The former is used to design specific terminal configurations which can be then simulated and evaluated by the latter. An application of the framework to a real container terminal expansion problem demonstrates the validity of the framework. Results obtained from simulation models generated efficiently by the framework are used to help terminal planners make reasonable decisions.